Physical Health problems among Iraqi Women with Ectopic Pregnancy - Essa, Sarah Flaieh; Ghafel, Hawraa Hussein (Journal of Contemporary Medical Sciences, 2021)
Objective: To assess physical health problems among women with ectopic pregnancy and to evaluate the levels of Physical health among women with ectopic pregnancy, and to identify demographic characteristics of ectopic pregnant women Methods: This study was conducted at maternity hospital in Karbala city in Iraq to assess the physical health problems of women with ectopic pregnancy. This study was started in January 2020 to March 2021, The data regarding women's health problems was achieved from the patient’s charts that recorded in the Statistical Department in the hospitals, the study consist of (40) women with ectopic pregnancy which were selected according to inclusion criteria (Women who had ectopic pregnancy, Women in reproductive age only). The data are analyzed through the use of descriptive and inferential statistics analysis procedures were employed for the data analysis. Result: The findings of the study exhibits that women with ectopic pregnancy were suffering from physical health problems such as (acute abdominal pain, tired and lethargic, faint, hypotension, vaginal bleeding, internal bleeding). The mean of scores for items related to physical health problems among women that show bad among most of items (1, 3, 4, 6, 7, 8, and 9) except item 2, 5, and 6 that show fair. Conclusion: The study concludes that women with ectopic pregnancy were suffering from physical problem such as (acute abdominal pain, tired and lethargic, faint, hypotension, vaginal bleeding, and internal bleeding).